2021
DOI: 10.3390/ma14133684
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sr-CoFe2O4 Nanoparticles with Different Particles Sized as Additives in CIP-Based Magnetorheological Fluid

Abstract: This study investigated the effect of adding strontium (Sr)-doped cobalt ferrite (CoFe2O4) nanoparticles in carbonyl iron particle (CIP)-based magnetorheological fluids (MRFs). Sr-CoFe2O4 nanoparticles were fabricated at different particle sizes using co-precipitation at calcination temperatures of 300 and 400 °C. Field emission scanning electron microscopy (FESEM) was used to evaluate the morphology of the Sr-CoFe2O4 nanoparticles, which were found to be spherical. The average grain sizes were 71–91 nm and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Substituting Equation (18) into Equation ( 8) to obtain the shear stress distribution equation in each region of the parallel plate model:…”
Section: Flow Binghammentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Equation (18) into Equation ( 8) to obtain the shear stress distribution equation in each region of the parallel plate model:…”
Section: Flow Binghammentioning
confidence: 99%
“…Based on the good electromechanical coupling characteristics of magnetorheological smart materials, great results are achieved in anti-vibration control, and it also provides the possibility for the shock buffer control design of electromechanical systems under complex conditions [17]. Wang et al proposed the application of magnetorheological damper to the recoil of artillery [18], which established a dynamic model of magnetorheological damper and discussed the application of magnetorheological damper in application on the anti-recoil device of the artillery. Subsequently, the team conducted research on the dynamic characteristics of the magnetorheological damper under the impact of the artillery barrel force [19].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetorheological fluid [1] (MRF) is an intelligent material consisting of magnetizable particles, flow carriers, and stabilizer additives [2]. The magnetorheological damper (MRD), which takes advantage of MRF, has a wide range of adjustable, fast response, low energy consumption, and "fail-safe" characteristics [3].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [17] studied rod-like γ-Fe 2 O 3 nanoparticles to improve the suspension stability of MR fluid. Besides, it has been confirmed that the size of the nanoparticles has an effect on both the MR properties and the suspension stability of MR fluid [18]. Shah et al [19] studied the performance of MR dampers filled with a low sedimentation MR fluid with plate-like iron particles at different time intervals.…”
Section: Introductionmentioning
confidence: 99%